Long non‐coding RNA DLX6‐AS1 mediates proliferation, invasion and apoptosis of endometrial cancer cells by recruiting p300/E2F1 in DLX6 promoter region - Zhao, Hui (J Cell Mol Med, 2020)
Endometrial cancer features abnormal growth of cells of the inner lining of the uterus with the potential to invade to other organs. Accumulating evidence suggests that aberrant expression of long non‐coding RNA (lncRNA) may facilitate cancer progression. The aim of the present study was to identify the molecular mechanisms of the lncRNA known as DLX6 antisense RNA 1 (DLX6‐AS1) in endometrial cancer. Microarray‐based analysis was utilized to predict expression profile and possible function pattern of DLX6‐AS1 and DLX6 in endometrial cancer, and their expression was quantified in 78 clinically obtained endometrial cancer tissues and also in cell lines. We next assessed the effects of DLX6‐AS1 and DLX6 on proliferation, invasion and apoptosis of endometrial cancer cells. A mouse xenograft model was established to confirm DLX6‐AS1 functions and explore its underlying regulatory mechanisms in vivo. DLX6‐AS1 and DLX6 were highly expressed in endometrial cancer tissues and cells, and their silencing weakened the proliferative and invasive abilities of endometrial cancer cells and tumours, while promoting apoptosis. Mechanistic investigations indicated that DLX6‐AS1 formed a triplex structure with DLX6 via interaction with p300/E2F1 acetyltransferase. Thus, we find that functional up‐regulation of DLX6‐AS1 can promote endometrial cancer progression via a novel triplex mechanism that may prove to be great clinical significance for future treatments of endometrial cancer.